Analyzing the role of mutual guarantee societies on bank capital requirements for small and medium-sized enterprises - Cardone Riportella, Clara (2013)
This paper analyzes the impact of the guarantee provided by mutual guarantee societies (MGSs) on the risk premium that banks should charge for small- and medium-sized enterprise (SME) loans under the new Basel Capital Accords (Basel II and III). We also examine whether the foreseeable decrease in the theoretical credit risk premium would be compensated by the cost of the MGS guarantee. To do so, we develop a rating system for SMEs that uses a large sample of Spanish firms over the period from 2005 to 2009. We find that the final effect of the guarantee on the SME risk premium depends on the values taken by the credit variables of the MGS (essentially, the probability of default).